2020
DOI: 10.1038/s41419-020-2473-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from mesenchymal stem cells repair a Parkinson’s disease model by inducing autophagy

Abstract: Parkinson's disease (PD) is a progressively debilitating neurodegenerative condition that leads to motor and cognitive dysfunction. At present, clinical treatment can only improve symptoms, but cannot effectively protect dopaminergic neurons. Several reports have demonstrated that human umbilical cord mesenchymal stem cells (hucMSCs) afford neuroprotection, while their application is limited because of their uncontrollable differentiation and other reasons. Stem cells communicate with cells through secreted ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(137 citation statements)
references
References 69 publications
1
135
1
Order By: Relevance
“…IL6, IL8, IL1β, TNFα, IFNα) that can further exacerbate the inflammatory response [60,114]. In recent years, the neuroprotective and anti-inflammatory properties of stem cell EVs have been well-documented; in the context of the CNS, there is accumulating evidence that stem cell EVs may be able to reverse neuronal apoptosis and modulate the polarization of both astrocytes and microglia from pro-inflammatory to anti-inflammatory phenotypes [81,82,83,84,85,86,87,88,89,90,91,92]. To the best of our knowledge, the functional effects of stem cell EVs on 3D cultures has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL6, IL8, IL1β, TNFα, IFNα) that can further exacerbate the inflammatory response [60,114]. In recent years, the neuroprotective and anti-inflammatory properties of stem cell EVs have been well-documented; in the context of the CNS, there is accumulating evidence that stem cell EVs may be able to reverse neuronal apoptosis and modulate the polarization of both astrocytes and microglia from pro-inflammatory to anti-inflammatory phenotypes [81,82,83,84,85,86,87,88,89,90,91,92]. To the best of our knowledge, the functional effects of stem cell EVs on 3D cultures has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…After confirming EV uptake by neurospheres we shifted our focus to next examine their potential functional effects in HIV-1 infected neurospheres. To date, the anti-apoptotic effects of stem cell EVs in the context of the CNS have been well documented both in vitro and in vivo [81,82,83,84,85,86]. To this end, we performed western blot to examine the expression levels of different proteins involved in the regulation of apoptosis ( Fig.…”
Section: The Effect Of Stem Cell Evs On Hiv-1 Infected Neurospheresmentioning
confidence: 99%
“…A similar approach was also evaluated for delivering dopamine to the striatum and substantia nigra of PD mouse model, confirming that the exosomes can be used as a promising drug delivery platform for target therapy against PD and other neurodegenerative diseases [ 145 ]. In a current study, Chen et al demonstrated that human umbilical cord mesenchymal stem cells (hucMSC)-derived exosomes can reach the substantia nigra through the BBB in vivo, reducing the dopaminergic neuron loss and apoptosis and upregulating the levels of dopamine in the striatum [ 146 ].…”
Section: Stem Cell-derived Exosomes As a Therapeutic Approach Formentioning
confidence: 99%
“…A research group demonstrated that human umbilical cord mesenchymal stem cell (hucMSC)-derived exosomes reduced apoptosis in SH-SY5Y cell culture. Further, in a PD rat model (6-OHDA lesioned), exosomes crossing the blood-brain barrier, reached the substantia nigra, decreased dopaminergic neurons loss and apoptosis, improved apomorphine-induced asymmetric rotation, and increased dopamine levels in the striatum [ 81 ].…”
Section: The Fate Of Msc-derived Secretomementioning
confidence: 99%